Unsteady natural convection flow of nanofluids past a semi-infinite isothermal vertical plate - Tippa, S. (American Institute of Physics Inc., 2016)
Numerical analysis is performed to investigate the unsteady natural convection flow of a nanofluid past a semi-infinite isothermal vertical plate. Five different types of water based nanofluids are considered in this investigation where Silver (Ag), Copper (Cu), Copper Oxide (CuO), Alumina (Al2O3) and Titanium Oxide (TiO2) are the nanoparticles. The governing non-dimensional partial differential equations are solved by employing an implicit finite-difference method of Crank-Nicolson type. Numerical results are computed for different values of pertinent parameters. The results for nanofluid temperature, velocity, local Skin friction and Nusselt number, average Skin friction and Nusselt number are discussed through graphs. The present numerical results for local Nusselt number have been compared with the well-established pure fluid correlation results for the limiting case and the comparison shows that the results are in excellent agreement. Â© 2016 Author(s).